2021
DOI: 10.1016/j.reth.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The immature platelet fraction affects the efficacy of platelet rich plasma therapy for knee osteoarthritis

Abstract: Introduction Platelet-rich plasma (PRP) therapy is used to treat pathological conditions such as degenerative inflammatory diseases including osteoarthritis (OA) by enhancing tissue repair and promoting anti-inflammatory effects. Although PRP therapy for patients with knee OA improved pain and functional scores, the association of clinical outcomes and quality of PRP including cell composition and concentration is unclear. Methods Therefore, this study analyzed blood ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The determinant contribution of Hy Tissue Tube 50 to efficacy could not be statistically demonstrated, but results deserve to be more extensively assessed in dedicated analysis with a higher number of patients with long term follow-up. However, we strongly believe that, more sophisticated surrogate markers of PRP bioactivity are needed to anticipate PRP-associated clinical efficacy, as recently suggested [ [45] , [46] , [47] ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The determinant contribution of Hy Tissue Tube 50 to efficacy could not be statistically demonstrated, but results deserve to be more extensively assessed in dedicated analysis with a higher number of patients with long term follow-up. However, we strongly believe that, more sophisticated surrogate markers of PRP bioactivity are needed to anticipate PRP-associated clinical efficacy, as recently suggested [ [45] , [46] , [47] ].…”
Section: Discussionmentioning
confidence: 98%
“…From a medico-economic perspective, repetition of PRP injections could be rather reserved to responder patients with reappearance of KOA symptoms with the aim to delay or avoid knee arthroplasty, as recently demonstrated by Sanchez et al. [ 47 ]. This raises the question of final price for PRP injection which vary from US$300 to US$600 in our dedicated centers while different studies reported a range from US$500 to US$2500 [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous evaluations of PRP effectiveness in similar cohorts (Japanese patients suffering from symptomatic knee OA) have been limited by small sample sizes, short follow-up duration, and variable PRP preparation methodologies [5,[12][13][14][15]. Previous studies have reported OMER-ACT-OARSI responder achievement of 58-78% of injected knees at between 1 and 24 months [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multivariate logistic regression showed that a high IPF% in whole blood was significantly associated with VAS amelioration. A low percentage of neutrophils in PRP was significantly associated with VAS amelioration and KOOS amelioration [59].…”
Section: The Immature Platelet Fraction Affects the Efficacymentioning
confidence: 93%